KOMUNIKASI ANTARPRIBADI ANTARA PRAMUWISATA DAN WISATAWAN - Surjani, Any; Parapat, Nelson Halong (Jurnal Insani, 2023)
This research starts from the question "how is interpersonal communication between tour guides and tourists?" The purpose of this research is to obtain an overview of the stages of interpersonal communication that guides and tourists go through, as well as personal disclosures that are carried out by guides and tourists. The research method used is descriptive qualitative. The research was conducted on five subjects, namely two tour guides who carried out the communication process with three tourists. The results of the study show that in traveling the subjects went through several stages of social penetration, namely the orientation stage, where subjects made introductions, shared their experiences and impressions when they first met. In the affective exploratory exchange stage, there is a discussion of personal relationships, with relaxed communication. The affective exchange stage, where at this stage pays attention to each other, time and opportunities until friendship is established between these respondents as evidenced by the existence of a relationship or closeness, so they can get to know and understand each other better. In the stable exchange stage, they begin to establish closeness and are more familiar as evidenced by the efforts of the two in working together and unifying opinions and thoughts. Self disclosure runs ideally in accordance with following the stages of the relationship based on the perspective of social penetration theory, both from impersonal to interpersonal, from strangers to acquaintances, having a good relationship and the closeness and familiarity between tour guides and tourists.